Alternative and Unconventional Feeds in Dairy Diets and Their Effect on Fatty Acid Profile and Health Properties of Milk Fat - Hadrová, Sylvie; Sedláková, Kateřina; Křížová, Ludmila; Malyugina, Svetlana (Animals, 2021)
Milk fat is an important nutritional compound in the human diet. From the health point of view, some fatty acids (FAs), particularly long-chain PUFAs such as EPA and DHA, have been at the forefront of interest due to their antibacterial, antiviral, anti-inflammatory, and anti-tumor properties, which play a positive role in the prevention of cardiovascular diseases (CVD), as well as linoleic and γ-linolenic acids, which play an important role in CVD treatment as essential components of phospholipids in the mitochondria of cell membranes. Thus, the modification of the FA profile-especially an increase in the concentration of polyunsaturated FAs and n-3 FAs in bovine milk fat-is desirable. The most effective way to achieve this goal is via dietary manipulations. The effects of various strategies in dairy nutrition have been thoroughly investigated; however, there are some alternative or unconventional feedstuffs that are often used for purposes other than basic feeding or modifying the fatty acid profiles of milk, such as tanniferous plants, herbs and spices, and algae. The use of these foods in dairy diets and their effects on milk fatty acid profile are reviewed in this article. The contents of selected individual FAs (atherogenic, rumenic, linoleic, α-linolenic, eicosapentaenoic, and docosahexaenoic acids) and their combinations; the contents of n3 and n6 FAs; n6/n3 ratios; and atherogenic, health-promoting and S/P indices were used as criteria for assessing the effect of these feeds on the health properties of milk fat.
Keywords: health; algae; tannins; indices; milk fat quality; dairy cows; herbs and spices; okara; camelina